Analisis Laporan Keuangan Berdasarkan SAK-ETAP pada PT ABC - Risti Dinar Larasati; Muslimin Muslimin (AKUNTANSI 45, 2024)
The company can improve its performance if the financial statements presented can be in accordance with applicable standards so that the information contained therein can be maximally useful. However, not all companies understand the provisions for presenting financial statements in accordance with applicable accounting standards, for example in the financial statements of PT ABC. Therefore, this research aims to analyze the financial statements presented by PT ABC for a certain period. PT ABC is a company without public accountability, so the presentation of its reports must be adjusted to the Financial Accounting Standards-Entities Without Public Accountability (SAK-ETAP). This research uses a qualitative method with the data used, namely secondary data and with a comparative descriptive analysis technique which aims to compare the financial statements of PT ABC with SAK-ETAP which provides narrative explanatory results. The results of this study are that PT ABC has not been able to fully present financial statements based on SAK-ETAP where there are still types of reports that are not presented but the items in the types of reports presented are in accordance with SAK-ETAP.